Análise da distribuição espacial de beribéri e de síndrome respiratória aguda grave por covid-19 - MAXIMINO, Flávio Donalwan Sá (2023)
Introduction: The location and distribution of diseases are fundamental in the epidemiological context of a society. Spatial analysis makes it possible to study geographic and spatial patterns of health and disease, assessing the relationships between spatial data and health. Objective: To discuss the importance of spatial distribution analysis as a health surveillance tool for neglected diseases and severe acute respiratory syndromes (SARIs). Method: This is a descriptive study, which addresses the analysis of the spatial distribution for two diseases: beriberi and SARS due to COVID-19. The first article is an ecological study with spatial distribution analysis, based on three databases: HORUS System (thiamine distribution); Ministry of Health (cases of beriberi) and Mortality Information System (deaths due to beriberi), from 2014 to 2020, in all federative units of Brazil. The second article is a descriptive study of SARS lethality rates by COVID-19 by municipality of notification and residence in Maranhão, based on records in the Information System for Epidemiological Surveillance of Influenza (SIVEP-Gripe), by municipalities of notification and of residence, from March 2020 to December 2022. Results: In the first study, 542 cases and 177 deaths from beriberi were recorded. Roraima and Tocantins registered the majority of cases (518; 95.5%), especially in the indigenous population (269; 49.6%). Cases predominated in men (405; 74.7%), rural areas (335; 61.8%) and with alcohol consumption (359; 66.2%). Deaths were more frequent in the white race/color (85; 48.0%), in São Paulo (36; 20.3%) and Minas Gerais (28; 15.8%). Indigenous establishments received a low quantity of thiamine tablets (1,381,141; 3.8%). In the second study, on SARS lethality due to COVID-19, 3,617 deaths were reported in 2020, 5,288 in 2021 and 588 in 2022. The lethality rate in the period was 39.1%, 45.3% in 2020; 36.4% in 2021; and 33.3% in 2022. The lethality rate by municipality of notification and residence was equal to 100% in 18 (8.2%) and five (2.3%) municipalities, respectively. 106 municipalities (48.8%) did not notify cases, while 129 municipalities (59.4%) did not register deaths. Conclusion: Beriberi is a neglected disease and is present in all regions, especially in poor, vulnerable areas with an indigenous population. Most cases are related to men, in rural areas, with alcohol consumption. Differences were found between lethality rates by municipality of hospitalization and municipality of residence. The data suggest that there are underreporting/underreporting of cases and deaths in SIVEP-Flu, changing SARS lethality rates due to COVID-19.